Blended brown coal and Class F fly ash based geopolymer - Md. Hamidul Islam; David Law; Yulin Patrisia; Chamila Gunasekara (Case Studies in Construction Materials, 2025)
Geopolymer concrete has been shown to be a suitable option to overcome the challenges of carbon emissions from Portland cement (PC) and the landfill storage of brown coal fly ash (BCFA). Earlier studies have demonstrated that geopolymer bricks made with high-crystalline BCFA achieve strengths of 5–15 MPa, while geopolymer concrete reaches around 30 MPa, but both require curing at 120 °C. This temperature is impractical for commercial brick production, as most manufacturing facilities operate at a maximum of 80 °C. To address these issues this study examines the compressive strength and microstructural evolution of BCFA and Class F fly ash (FA) blended geopolymer mortar at 80 °C curing. The study employs different sodium hydroxide-to-sodium silicate activator ratios. The Na2O dosage is fixed at 15 % over a range of Alkali Modulus (AM), 1.0, 1.25, 1.50 and 1.77. The study utilizes an extensive range of characterization and microscopy techniques to study the evolution of the hydration process. The study identifies 15 % Na2O and AM 1.25 as optimum alkali activator dosages. This achieves a 40 % utilization of BCFA (B40–1.25) with a concrete strength of 39.40 MPa (7 days) and 38.97 MPa (28 days). In addition, this optimum design with 70 % utilization of BCFA attained strengths of 18.92 and 23.30 MPa at 7 and 28 days, respectively, suitable for brick production. The formation of N-A-S-H and/or C-A-S-H gel combined with the crystalline phases of the optimum mix (70 % BCFA and 30 % FA) are primarily responsible for achieving these strengths at the reduced curing temperature of 80 °C.